Book Reviews - Brian van Wyk; Shandir Ramlagan; Sharon Kleintjes (Taylor & Francis Group, 2005)
Letting Them Die: Why HIV/AIDS Prevention Programmes Fail By Catherine Campbell, Cape Town, South Africa: Double Storey Books, 2003, ISBN 1-919-930116. Reviewed by Brian van Wyk.The Moral Economy of AIDS in South Africa By Nicoli Nattrass. New York: Cambridge University Press, 2004. ISBN 0-521-54864-0. Reviewed by Shandir Ramlagan.Learning from HIV and AIDS Edited by George Ellison, Melissa Parker, and Catherine Campbell. 2003. New York: Cambridge University Press, ISBN 0-521-80866-9, 0-521-00470-5pbk. Reviewed by Sharon Kleintjes.